Dirección estratégica en empresas familiares: Caso Plásticos Fayco (2017)
The strategic direction is based on the interest of making the most of the internal and external state in which an organization finds itself, it pretends that every decision taken is an active and congruent step that leads to the achievement of objectives and goals; Family companies are the pillar of much of the world economy, they are born with the interest of generating an autonomous and sustainable income that will last for present and future generations. The analysis is done in the city of Barranquilla and hand in hand with the University of the Coast with a type of descriptive study with scope of case study; the method of study is deductive, with a design of non-experimental transactional or transverse research of quantitative epistemological approach. It is possible to conclude the absence of academy in the performance of the family business; these achieve a sustainable evolution over the years thanks to their labor precepts but not for the development of strategies, market analysis and internal improvements. It is recommended, among other things, to have an impartial leader, listen to what internal and external clients are willing to contribute, be flexible without losing sight and mission, allow the family to integrate, generate value, compare and apply success case processes that may impact on the improvement of the economic activity of the company.